Simplified volume equations for grey poplar (Populus × canescens Smith.) standing trees - Ábri, Tamás; Honfy, Veronika; Rédei, Károly (Acta Agraria Debreceniensis, 2024)
Grey poplar (Populus× canescens Smith.) is a natural hybrid of white poplar (Populus alba L.) and Eurasian aspen (Populus tremula L.). It can be found throughout Europe, where both parents are present. The above mentioned species of poplars (under the term of ‘domestic poplars’) cover approximately 5% of the forests of Hungary. Of these species, grey poplar holds significance in forestry, and its role in afforestation shows a growing tendency. For this reason, improving the growing technology of grey poplar is a timely topic. In this paper we introduce algorithms which help estimate grey poplar tree volumes without having to use volume tables. Based on the performed evaluations, both equations can be used for single tree volume estimation with an error of less than 5%.